2023
DOI: 10.3390/jcm12093049
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Optical Coherence Tomography Biomarkers in Neovascular Age-Related Macular Degeneration

Abstract: Optical coherence tomography has revolutionized the diagnosis and management of neovascular age-related macular degeneration. OCT-derived biomarkers have the potential to further guide therapeutic advancements with anti-vascular endothelial growth factor; however, the clinical convergence between these two tools remains suboptimal. Therefore, the aim of this review of literature was to examine the current data on OCT biomarkers and their prognostic value. Thirteen biomarkers were analyzed, and retinal fluid ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Our recent study found that patients with MA had shown significantly lower improvement in BCVA. The generally worse outcome of anti-VEGF therapy in eyes with pre-existing MA is supported by previously published papers [51,52].…”
Section: Discussionmentioning
confidence: 57%
“…Our recent study found that patients with MA had shown significantly lower improvement in BCVA. The generally worse outcome of anti-VEGF therapy in eyes with pre-existing MA is supported by previously published papers [51,52].…”
Section: Discussionmentioning
confidence: 57%
“…AMD is a progressive, degenerative retinal disease typically seen in individuals of advanced age [ 26 , 27 ]. It is characterized by abnormalities of macular photoreceptors, RPE, Bruch membrane, and choroid, resulting in loss of central vision.…”
Section: Activation Of the Complement System In Retinal Diseasementioning
confidence: 99%